Effect of desing parameters on CAM profiles (2003)
"In the process of generating a cam profile, input parameters such as lift maximum allowable pressure angle, eccentricity and roller radius are subjected to variations. These variations are done in order to arrive at optimum output design parameters, cam profiles and ultimately optimum cam design. A computer aided analysis of cam profiles with eight - order - polynomial motion using a roller follower and having a Dwell- Rise - Return. displacement profile has therefore being carried out in this work. The analysis, in a similar procedure, is also applicable to cam profiles with different standard cam motions, followers, displacement profiles and cam angles. The followers lift, maximum allowable pressure angle, eccentricity and roller radius were varied within and outside design limits and their effects ana lysed on the generated cam profiles and other design parameters. Optimum values for the parameters considered were obtained from the result of the variation analysis, while characteristic changes were also observed from the generated cam profiles. "